persetubuhan mayat Kualifikasi Persetubuhan Mayat Perempuan Dalam Hukum Pidana - Nur Riska Aulia; Ivan Zairani Lisi; Rini Apriyani (Law Department, University of Widya Gama Mahakam Samarinda, 2025)
Background: The act of sexual intercourse that occurs in women is not a small number, the view of criminal acts against sexual intercourse in the beginning was only limited to someone who was still alive. However, with the development of the era and technology, the act of sexual intercourse can also be done to women who have died and this act is an immoral and indecent act. This act is related to moral norms, a person's honor. Research Metodes: Research with a doctrinal approach is directed at a set of norms as research targets through analysis of relations between norms, content analysis, the combination of norm theories, and legal principles. The doctrinal approach does not avoid the use of certain factors with assumptions as supporters of research analysis. This research focuses on a set of norms, the basis of the argumentation built comes from a set of legal norms that have been regulated but are not sufficient. Findings: The act of sexual intercourse with a deceased woman is an immoral act and violates the rights and dignity of the deceased/corpse according to positive law in Indonesia and can be prosecuted under Article 271 of the New Criminal Code, and in fact the act of sexual intercourse with a deceased woman cannot be qualified as a criminal act of treating a corpse in an uncivilized manner because the formulation in Article 271 of the New Criminal Code does not fulfill the principle of lex certa so it is less explicit when applied to the act. Conclusion: Criminal law policy can pay attention to the principles of criminal law; Refer to the Sexual Offences Act 2003 which clearly and firmly regulates sexual intercourse with a deceased person; Make comparisons by looking at the similarities and differences of Regulations with other countries, as a reference in resolving cases of sexual intercourse with deceased objects.